Perjuangan Minoritas Muslim dan Perkembangan Pemikiran Tasawuf di China - M. Arrafe Abduh (An-Nida', 2013)
Congregation (menhuan) Naqsyabandiyah in China, there are also followers in Indonesia, the Chinese of martial arts martial arts long before the Ming Dynasty (1368-1644 AD). Kung Fu Kick Muslim Hui people Tan Tui, Zhaquan, Baijiquan, Qishiquan, Piquaquan and Shiba and respiratory system.In the era of the Yuan dynasty (1279-1368 AD) and the Ming dynasty (1368-1644 AD), Their mastery of Confucianism is a consequence of the policies implemented in the early shinisme power Ming Dynasty. In addition to not reject traditional Chinese ancestral culture, understanding of Confucianism, because they want to attract the sympathy of the Chinese Muslims and the Islamic world in order to easily establish diplomatic and economic relations.